2021
DOI: 10.3390/polym13081286
|View full text |Cite
|
Sign up to set email alerts
|

Mechanically Sustainable Starch-Based Flame-Retardant Coatings on Polyurethane Foams

Abstract: The use of halogen-based materials has been regulated since toxic substances are released during combustion. In this study, polyurethane foam was coated with cationic starch (CS) and montmorillonite (MMT) nano-clay using a spray-assisted layer-by-layer (LbL) assembly to develop an eco-friendly, high-performance flame-retardant coating agent. The thickness of the CS/MMT coating layer was confirmed to have increased uniformly as the layers were stacked. Likewise, a cone calorimetry test confirmed that the heat r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 42 publications
0
9
0
Order By: Relevance
“…With the increasing concern on environmental issues and the depletion of fossil resources, bio-based FRs have received more and more attention. [144][145][146] Bio-based compounds, such as cellulose, 86,147,148 starch, [149][150][151] cyclodextrin, 30,152,153 chitosan, 154 phytic acid, [155][156][157][158][159][160][161][162] and lignin, [163][164][165] can be used as highly effective green FR additives due to their excellent char-forming ability. During the combustion process of the material, bio-based FRs promote char formation on the surface, insulate the diffusion of oxygen and heat and inhibit further combustion.…”
Section: Bio-based Frsmentioning
confidence: 99%
“…With the increasing concern on environmental issues and the depletion of fossil resources, bio-based FRs have received more and more attention. [144][145][146] Bio-based compounds, such as cellulose, 86,147,148 starch, [149][150][151] cyclodextrin, 30,152,153 chitosan, 154 phytic acid, [155][156][157][158][159][160][161][162] and lignin, [163][164][165] can be used as highly effective green FR additives due to their excellent char-forming ability. During the combustion process of the material, bio-based FRs promote char formation on the surface, insulate the diffusion of oxygen and heat and inhibit further combustion.…”
Section: Bio-based Frsmentioning
confidence: 99%
“…As mentioned above, except for the chitosan, another renewable and bio-based material that can be applied in LbL flame retardant coatings for polyurethanes is starch. Choi et al [202] used it to prepare simple starch/MMT bilayer LbL coatings using sprayassisted assembly. The efficiency of the coating comprised of five bilayers was confirmed by a 22.7% drop of pHRR and a 52.7% reduction of THR comparing to the uncoated foam.…”
Section: Coating Andmentioning
confidence: 99%
“…Generally, bio‐based FRs are modified to produce bio‐based materials or mechanically blended with other high‐efficiency FRs. Studies have found that biomacromolecules such as cellulose, lignin, phytic acid, chitosan, and starch can be used in PLA to improve flame retardancy 35–38 …”
Section: Introductionmentioning
confidence: 99%
“…Studies have found that biomacromolecules such as cellulose, lignin, phytic acid, chitosan, and starch can be used in PLA to improve flame retardancy. [35][36][37][38] Casein is the most important protein in mammals and is a phosphoprotein. Furthermore, it has attracted the attention of researchers as a bio-based FR.…”
Section: Introductionmentioning
confidence: 99%